Cyberphysical Systems: The Fundament of Smart Economy - YershovaО. L.; ОdnovolykV. І.; BazhanL. І. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The article deals with the key technological trends underlying cyberphysical systems. The questions of constructing the smart industry as a cyber-physics system are described in their context the, barriers and risks are described in the transition to smart technologies in the economy and ways of overcoming them. The combination of the Internet and material things forms new opportunities for managing the physical world, including devices, factories and infrastructure that determine the modern economic landscape. The next 10 years of Internet of Things can radically change the manufacturing industry, energy, agriculture, transport and other sectors of the real economy, accounting for almost two thirds of world GDP. Due to the processes of digitization, such transformations will have far-reaching consequences in terms of redistribution of resources and markets of the present world. Technically, the smart industry integrates advances in the field of physical devices with advances in the field of information and communication technologies, which results in the formation of cyber-physics systems. For Ukraine, the special significance of smart industry is also determined by the fact that its traditional industry is currently in crisis, and the new “smart” industry has not received enough attention from the state. In the developed plan, the government’s priority actions in the Ukrainian economy for the period up to 2020 are smart industry (Industry 4.0, Internet industry, advanced digital production, etc.), unlike US, China, EU countries and other industrial leaders in general not considered, especially as a national strategic investment. The possibilities of using cyber-physics systems in various branches of economy and socially important systems are described. Examples of smart manufacturing are presented in modern conditions of Ukraine.